Post downsizing assessment among downsizing survivors, and downsized employees in finance sector - Bashirrad, Ashkan (My University, 2006)
Bu araştırma 2001 ekonomik kriz sonrası mali sektorde işten çıkartılan ve işte kalmayı başaranlar arasında 2002 yazında yapılmıştır. Bu iki grup arasında ve içerisinde karşılaştırmalar yapabılmek için Organizasyona Bağlılığı, Organizasyonel Stres Etkenleri, Olay Sonrası Ölçeği, Minesota Tatmin Anketi MSQ ve Kariyer Beklentisi Anket ölçekleri kulanarak bu iki grubun karşılaştırmaya amaçlanmıştır.

This research has been made amongst Downsized Employees and Downsizing Survivors of Financial sector in Turkey after economic crisis of 2001, in summer 2002. This study has utilized several measurements such as Organizational Commitment, Job Stressors, Impact of Event Scale, Avoidance, MSQ, and Career Expectations amongst Downsizing survivors and Downsized Unemployed. It is tried to show relationships within and between these two groups. TABLE OF CONTENTS ACKNOWLEDGEMENTS: iii ÖZET iv ABSTRACT v TABLE OF CONTENTS vi LIST OF TABLES ix 1. INTRODUCTION 1 2. LITERATURE SURVEY Voluntary and Involuntary Turnover 3 2.1. Differentiating between Voluntary and Involuntary Turnover 3 2.2. Attractions and Distraction of Voluntary Turnover4 2.3. Attractions and Distraction of Voluntary Involuntary Turnover 5 3. DOWNSIZING 6 3.1. Management of Downsizing Organizational Level 10 3.2. Employees Response to Downsizing: Survivor Employee Level 11 3.2.1. Psychological Reactions 11 3.2.2. Job Insecurity amongst the Survivors 11 3.3. Downsizing: Downsized Employee Level 12 3.4. Downsizing Association with Commitment, Satisfaction, and Stress 13 3.4.1. Organizational Commitment and Involvement 15 3.4.2. Satisfaction, Organizational Commitment and Turnover Behavior 17 4. AVERAGE IMPACT of UNEMPLOYMENT after DOWNSIZING 20 4.1. Predictors of the Impact of Job Loss 20 4.2. Economic Hardship 21 4.3. Employment Commitment 21 4.4. Time Structure 22 4.5. Downsizing and Social Support 22 4.5.1. Eroding Social Support on the Job 23 4.5.2. Coping Techniques and Methods 24 4.6. Post Downsizing Effects 25 4.6.1. Stress 27 4.6.2. Organizational Stressor 28 4.6.2.1. Personal Stressors 30 4.6.2.2. Interpersonal Stressors 30 4.6.2.3. Organizational Stressors 30 4.6.2.4. Environmental Stressors 30 4.6.2.5. Private Life Stressors 30 4.6.3. Downsizing as Traumatic Events 31 4.6.3.1. Trauma 31 4.6.3.2. Posttraumatic Stress 32 4.6.3.3. Posttraumatic Stress Disorder 33 4.6.3.4. Requirements for Posttraumatic Stress Disorder (PTSD)34 5. RESEARCH36 5.1. Planning of the Study 36 5.2. Research Questions 37 5.3. Subjects 37 5.3.1. Downsizing Survivors 37 5.3.2. Downsized Employees 38 5.4. Instruments 38 5.4.1. Downsizing Survivor Employees Level Implemented Questionnaire: 38 5.4.1.1. Organizational Commitment Scale 38 5.4.1.2. Organizational Stressor, Demographic Variables, and Felt Stressor 39 5.4.2. Downsized Employee Level Questionnaire 41 5.4.2.1. Impact of Event Scale (IES Scale) 41 5.4.2.2. Avoidance Questionnaire 42 5.4.3. Downsized and Survivor Employee Level Questionnaire 42 5.4.3.1. Job Satisfaction Questionnaire MSQ 42 5.4.3.2. Career Expectation 44 5.4.2.5. Demographics 45 5.5. Procedure 45 6. Data Analysis and Findings 46 6.1. Downsizing Survivor Employees 46 6.2. Downsized Employees 55 6.3. Downsized and Downsizing Survivor Employees Combined Assessment 63 7. DISCUSSION and CONCLUSION 66 REFERENCES 68 CITED REFERENCES74 Appendix 1: Downsizing Survivor Employee Level Questionnaire 77 Appendix 2: Downsized Employee Level Questionnaire 85 Notes92
Keywords: İnsan Kaynakları Yönetimi; İş Stresi; İş Tatmini; Kriz